PREVAPIX-ALL: Apixaban Compared to Standard of Care for Prevention of Venous Thrombosis in Paediatric Acute Lymphoblastic Leukaemia (ALL)—Rationale and Design - O'Brien, Sarah H.; Li, Danshi; Mitchell, Lesley G.; Hess, Thomas; Zee, Pamela; Yee, Donald L.; Newburger, Jane W.; Sung, Lillian; Rodriguez, Vilmarie (Thrombosis and Haemostasis, 2019)
Venous thromboembolic (VTE) complications in children and adolescents with acute lymphoblastic leukaemia (ALL) and T or B cell lymphoblastic lymphoma (T/B cell LL) can result not only in life-threatening acute complications but also contribute to significant long-term sequelae. The PREVAPIX-ALL study is an open-label randomized controlled study comparing outcomes of treatment with prophylactic dose apixaban versus no anticoagulation (standard of care) in children and adolescents with ALL and T/B cell LL receiving standard induction chemotherapy with asparaginase and the presence of a central venous access device. On day 29 of induction, all patients undergo screening imaging with duplex ultrasonography and echocardiography. The primary efficacy endpoint of the study is a composite of symptomatic and asymptomatic VTE that includes deep vein thrombosis, pulmonary embolism, cerebral sinovenous thrombosis or VTE-related death. The primary safety outcome is major bleeding. Secondary outcomes are central line-associated infections, patency and line replacement, superficial thrombosis, arterial events and death. A planned sample size of 500 randomized paediatric patients enrolled over a period of 5 years is based on the estimation of VTE rates of 20 and 10% in the standard of care and apixaban groups, respectively. An optional biomarker study in 150 patients will examine predictors of increased VTE risk and study in vivo anticoagulant effects of apixaban in children by measuring specific biomarkers in the haemostatic system and inflammatory pathway. This study will provide valuable information for the safety and efficacy of apixaban in VTE prevention during induction in paediatric ALL.
Keywords: anticoagulation; deep vein thrombosis; direct-acting oral anticoagulant; thromboprophylaxis; children